PANDEMI COVID-19 DAN PEREMPUAN SEBAGAI KEPALA RUMAH TANGGA DALAM KEMISKINAN URBAN DI BANDA ACEH - Muhammad Sauqi; Cut Risya Varlitya; Muhammad Ilhamsyah Siregar (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2022)
This study aims to analyze the comparison of urban poverty in Banda Aceh City in poor female-headed of households before and during the Covid-19 pandemic. This analysis uses a hypothesis-based qualitative method using the One Way Anova test and utilizes primary data obtained from the distribution of questionnaires, observations, and in-depth interviews with females as heads of poor households from 40 respondents. The results showed that most of the respondents of productive age were housewives and about 50 percent of the respondents only graduated from junior high school/equivalent, 93 percent had never attended training, 55 percent had no savings. Expenditure on respondents' basic needs decreased during Covid-19, namely, there was an expenditure of less than Rp300,000 per month which was above it before the outbreak occurred. Before the pandemic, there were no respondents who earned less than Rp350,000, but during the pandemic, 2.5 percent of respondents were found who earn less than Rp350,000 per month. Before the pandemic, 45 percent of respondents chose an average income ranging from Rp550,000 – Rp 1,500,000 per month, but this figure changed very significantly during the outbreak, namely the average income was only Rp450,000 – Rp550,000 per month, which is 50 percent of respondents. The One Way Anova test shows that there are differences in poor female-headed households spending before and during the Covid-19 pandemic.